2007
DOI: 10.1111/j.1741-3729.2007.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Deployment and Youth in Military Families: Exploring Uncertainty and Ambiguous Loss*

Abstract: Parental deployment has substantial effects on the family system, among them ambiguity and uncertainty. Youth in military families are especially affected by parental deployment because their coping repertoire is only just developing; the requirements of deployment become additive to normal adolescent developmental demands. Focus groups were used to inquire about uncertainty, loss, resilience, and adjustment among youth aged 12-18 that had a parent deployed, most often to a war zone. The nature of uncertainty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
238
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(249 citation statements)
references
References 28 publications
7
238
1
1
Order By: Relevance
“…Although wives could have transferred roles and responsibilities back to service members postdeployment, not all did, noting the desire to avoid the need to readjust again should a future deployment occur -a practical level ambiguity (Huebner et al, 2007). Wives, for the most part, had little choice but to learn to be selfreliant and perform all the household duties single-handedly while their service members were deployed.…”
Section: Managing Changesmentioning
confidence: 99%
“…Although wives could have transferred roles and responsibilities back to service members postdeployment, not all did, noting the desire to avoid the need to readjust again should a future deployment occur -a practical level ambiguity (Huebner et al, 2007). Wives, for the most part, had little choice but to learn to be selfreliant and perform all the household duties single-handedly while their service members were deployed.…”
Section: Managing Changesmentioning
confidence: 99%
“…En sus de ces défis, les familles de militaires doivent composer avec des facteurs déstabilisants propres à leurs conditions de travail qui complexifient leur quotidien et influencent la façon dont les rôles et responsabilités s'y inscrivent. Plusieurs des écrits scientifiques portant sur les familles de militaires s'intéressent aux particularités de leur mode de vie (Harrison, 2006;Huebner, et collab., 2007;Drummet, Coleman et Cable, 2003;Basham, 2008;Briggs et Atkinson, 2006), mais en dépit du nombre élevé de pères militaires, peu d'études portent sur les spécificités liées à leur rôle.…”
Section: Introductionunclassified
“…Several other American studies have found that children experience emotional distress during parental deployment (Barker & Berry, 2009;Chandra, Martin, Hawkins & Richadson, 2009;Huebner & Mancini, 2005;Huebner, Mancini, Wilcox, Grass & Grass, 2007,Tunac de Pedro et al, 2011. They have recognised that schools have an important role in play in supporting students through a parental deployment.…”
Section: Literature Reviewmentioning
confidence: 99%